Dampak Alih Fungsi Lahan Pertanian ke Non Pertanian Terhadap Tingkatan Konflik dan Manajemen Konflik di Subak Bau Kabupaten Gianyar - MARTHA, I MADE ARYA WIRA; DIARTA, I KETUT SURYA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
The Effect of Agriculture Land Conversion into Non-Agriculture Land toward Conflict Level in Subak Bau, Gianyar Regency The transfer of the function of agricultural land to non-agriculture in Subak Bau involves a very broad dimension. This can lead to conflicts that occur either internally or with outsiders. With this, a management of conflict handling in Subak Bau is required through compromise and collaboration or problem solving. The transfer of the function of agricultural land to non-agriculture will result in the impact of land conversion on economic resilience, social security, and the ecological resilience of the farming community. The purpose of this study was to analyse the level of conflict in Subak Bau and the efforts made to manage conflicts that occurred, and describe the impact of the conversion of agricultural land on social, economic, and ecological resilience. The method used in this study was a qualitative analysis method with interviews and quantitative analysis method with surveys. In Subak Bau there was a conversion of 2.71 hectares of agricultural land to nonagriculture. There were several levels of conflict and management efforts made for problem solving through compromise and collaboration or problem solving. The shift in the function of agricultural land to non-agriculture in Subak Bau had a negative impact on economic resilience, social security, and ecological resilience for farmers.The Effect of Agriculture Land Conversion into Non-Agriculture Land toward Conflict Level in Subak Bau, Gianyar Regency The transfer of the function of agricultural land to non-agriculture in Subak Bau involves a very broad dimension. This can lead to conflicts that occur either internally or with outsiders. With this, a management of conflict handling in Subak Bau is required through compromise and collaboration or problem solving. The transfer of the function of agricultural land to non-agriculture will result in the impact of land conversion on economic resilience, social security, and the ecological resilience of the farming community. The purpose of this study was to analyse the level of conflict in Subak Bau and the efforts made to manage conflicts that occurred, and describe the impact of the conversion of agricultural land on social, economic, and ecological resilience. The method used in this study was a qualitative analysis method with interviews and quantitative analysis method with surveys. In Subak Bau there was a conversion of 2.71 hectares of agricultural land to nonagriculture. There were several levels of conflict and management efforts made for problem solving through compromise and collaboration or problem solving. The shift in the function of agricultural land to non-agriculture in Subak Bau had a negative impact on economic resilience, social security, and ecological resilience for farmers.